Performance indicators related to points scoring and winning in international rugby sevens - Higham, D. G.; Hopkins, W. G.; Pyne, D. B.; Anson, J. A. (Journal of Sports Science & Medicine, 2014)
Identification of performance indicators related to scoring points and winning is needed to inform tactical approaches to international rugby sevens competition. The aim of this study was to characterize team performance indicators in international rugby sevens and quantify their relationship with a team`s points scored and probability of winning. Performance indicators of each team during 196 matches of the 2011/2012 International Rugby Board Sevens World Series were modeled for their linear relationships with points scored and likelihood of winning within (changes in team values from match to match) and between (differences between team values averaged over all matches) teams. Relationships were evaluated as the change and difference in points and probability of winning associated with a two within- and between-team standard deviations increase in performance indicator values. Inferences about relationships were assessed using a smallest meaningful difference of one point and a 10% probability of a team changing the outcome of a close match. All indicators exhibited high within-team match-to-match variability (intraclass correlation coefficients ranged from 0.00 to 0.23). Excluding indicators representing points-scoring actions or events occurring on average less than once per match, 13 of 17 indicators had substantial clear within-team relationships with points scored and/or likelihood of victory. Relationships between teams were generally similar in magnitude but unclear. Tactics that increase points scoring and likelihood of winning should be based on greater ball possession, fewer rucks, mauls, turnovers, penalties and free kicks, and limited passing.